2014
DOI: 10.3174/ajnr.a4157
|View full text |Cite
|
Sign up to set email alerts
|

The Computational Fluid Dynamics Rupture Challenge 2013—Phase I: Prediction of Rupture Status in Intracranial Aneurysms

Abstract: BACKGROUND AND PURPOSE: Rupture risk assessment for intracranial aneurysms remains challenging, and risk factors, including wall shear stress, are discussed controversially. The primary purpose of the presented challenge was to determine how consistently aneurysm rupture status and rupture site could be identified on the basis of computational fluid dynamics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 26 publications
1
52
0
Order By: Relevance
“…Recent advances in computational fluid dynamics (CFD) have enabled us to evaluate the hemodynamics of intracranial aneurysms with increasing reliability and accuracy. [19][20][21][22][23] Using state-of-the-art techniques, several studies have reported the influence of blood flow on the results of coil embolization for intracranial aneurysms. [24][25][26][27][28][29] In this study, we investigated the hemodynamics of basilar tip aneurysms with special attention to the volume of blood flow into aneurysms through the neck.…”
mentioning
confidence: 99%
“…Recent advances in computational fluid dynamics (CFD) have enabled us to evaluate the hemodynamics of intracranial aneurysms with increasing reliability and accuracy. [19][20][21][22][23] Using state-of-the-art techniques, several studies have reported the influence of blood flow on the results of coil embolization for intracranial aneurysms. [24][25][26][27][28][29] In this study, we investigated the hemodynamics of basilar tip aneurysms with special attention to the volume of blood flow into aneurysms through the neck.…”
mentioning
confidence: 99%
“…9, 12 Our hemodynamics RRS model was validated in another 85 aneurysms by our Buffalo-based research group. 12 Furthermore, this model was able to correctly distinguish ruptured MCA aneurysms from unruptured MCA aneurysms and also predicted the rupture region for the ruptured MCA aneurysms in the 2013 CFD challenge; 23 in addition, our hemodynamics RRS model was able to accurately predict the two ruptured MCA aneurysms from the three unruptured MCA aneurysms with similar size and shape in the 2015 CFD challenge (Varble N, Meng H: unpublished data, February 2015). Although RRS can potentially detect a high similarity of new IAs to already ruptured IAs in our cohort, future longitudinal studies should investigate the ability of RRS to predict eventual rupture.…”
Section: Discussionmentioning
confidence: 89%
“…20, 21 Three recent CFD challenges, in 2012, 22 2013, 23 and 2015 (http://cfdchallenge2015.c.ooco.jp/index2.html), have pushed the frontiers of image-based CFD for IAs. In the 2015 CFD challenge, 28 groups of CFD researchers were asked to predict the rupture status for 5 ruptured MCA aneurysms through hemodynamics calculation.…”
Section: Discussionmentioning
confidence: 99%
“…Zero‐pressure boundary conditions were imposed at all outlets. While this boundary condition does not necessarily lead to a physiological flow split between the outlet branches, it is used in many CFD studies because of the difficulty of determining patient‐specific values of the outlet resistances . The other commonly used way to compute flow splits between arterial branches, the Murray law, has been found to be violated in the circle of Willis .…”
Section: Methodsmentioning
confidence: 99%